2004
DOI: 10.4081/ijas.2004.323
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bacterial protein meal grown on natural gas on growth performance and carcass traits of pigs

Abstract: Bacterial protein meal (BPM), a new protein feedstuff produced by bacteria (Methylococcus capsulatus, Alcaligenes acidovorans,
Bacillus brevis and Bacillus firmus) grown on natural gas, was evaluated as a protein source for pigs. Two
growth trials were conducted, one with growing-finishing pigs and one with pigs from weaning until slaughter. In Exp. 1,
18 pigs fed restrictively (26.0 and 109.4 kg initial and final weight) were used to determine the effect of dietary inclusion
of BPM (0, 60,…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 15 publications
3
13
0
Order By: Relevance
“…The final dried product is a reddish/brown meal comprising approximately 96% dry matter, 70% crude protein, 10% lipids, and 7% ash. The amino acid composition of BPM resembles that of fish meal and soybean meal (SBM) with minor differences (Skrede et al 1998;Øverland et al 2004). Approximately 12% of N in BPM is derived from nucleic acid N in RNA and DNA, although the RNA and DNA contents are relatively low compared to those of other bacterial protein sources (Braude et al 1977;Kiessling & Askbrandt 1993).…”
Section: Introductionmentioning
confidence: 98%
“…The final dried product is a reddish/brown meal comprising approximately 96% dry matter, 70% crude protein, 10% lipids, and 7% ash. The amino acid composition of BPM resembles that of fish meal and soybean meal (SBM) with minor differences (Skrede et al 1998;Øverland et al 2004). Approximately 12% of N in BPM is derived from nucleic acid N in RNA and DNA, although the RNA and DNA contents are relatively low compared to those of other bacterial protein sources (Braude et al 1977;Kiessling & Askbrandt 1993).…”
Section: Introductionmentioning
confidence: 98%
“…However, the analyses showed that there was no difference in the trp content of the BPM diet compared with the CTRL diet. Previous analyses have shown that the bacterial protein meal can contain approximately 10-114% more trp than the current batch (Skrede et al 1998;Øverland et al 2004;Storebakken et al 2004;Skrede and Ahlstrøm 2004;Schøyen et al 2005;Øverland et al 2006). The variation in trp content of different batches of bacterial protein meal needs to be further investigated, especially since the present study indicates reduced fear after dietary trp enrichment.…”
Section: Discussionmentioning
confidence: 96%
“…The lack of effects of the BPM diet, corresponding to that seen for the trp diet, can partially be a result of the lower than expected trp content of the bacterial protein meal used in this study. Calculated from table values (Skrede et al 1998;Øverland et al 2004;Ahlstrøm et al 2004;Rouvinen-Watt et al 2005), the diets contained the following amounts of trp as fed: CTRL 0.34%, BPM 0.57% and TRP 2.01%. However, the analyses showed that there was no difference in the trp content of the BPM diet compared with the CTRL diet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations